(3gOGjI GdEfSGf daVd WGYI GdEeGes ((3Gdedhc LGQHQOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM dfG HaGJMI GdcJGH CHhGH GdLfGf CMeOg ef cJHJ dg JQGg ef GdfjQGf hGTcQ Ydi bHhd GdJhHI heRjO GdEMSGf s
(3BNQgG (B:s
(3Gf Gddg JYGdi Ndb OGQjf OGQ GdOfjG hOGQ GdBNQI hHGdSWGf GdYGOd bjGe GdOGQjf hHg jfJaY GdYHGO hGdHdGO hGdMeO ddg QH GdYGdejf s
(3GdeNWhWI HQSe GdebGe GdTQja Gdedc GdCTQa CHh GdfUQ bGfUhI GdZhQis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdSjGSI hGdGLJeGYs